Increasing teachers' self-efficacy through regular teaching and learning supervision - Khun-Inkeeree, Hareesol; Mahmood, Mohd-Hibatul-Hakimie; Haji-Mohd-Noo, Siti-Saadiah; Kasa, Muhammad Dzahir; Mohd Yaakob, Mohd Faiz; Omar-Fauzee, M. S; Mohd Sofian, Fatimah Noor Rashidah (Horizon Research Publishing, 2020)
Circular Letter No 3/1987 issued by the Ministry of Education of Malaysia makes it clear that the supervision of teaching and learning in the classroom is the responsibility of the principal or headmaster to fulfill his role as supervisor. However, school administrators are still not emphasizing this dimension of teaching and teaching supervision, as a result, there may be shortcomings in the pedagogical skills and the quality of the teaching material of teachers. Recognizing the importance of supervisory processes to enhance teacher professionalism, this study was conducted to examine the relationship between teaching and learning supervision skills and teacher self-efficacy, as well as to examine the influence of teaching and learning supervision dimensions on teaching effectiveness. This study was conducted among 211 teachers who participated in the teaching and learning supervision process in 13 primary schools selected by the Jeli District Education Office, Kelantan. The questionnaire was used to collect data and information. Correlation analysis showed that there was a significant relationship between supervisory skills and teacher self-efficacy (r=0.44, p=0.00), while regression analysis to examine the influence of teaching and learning supervision showed that the technical dimension was moderate (r=0.43, r2=0.185, p<0.05) and the knowledge dimension was also moderate (r=0.45, r2=0.200, p<0.05). This finding clearly shows that the quality of teaching and learning supervision will contribute to increased self-efficacy of teachers. The study also shows that the dimension of knowledge skills has the greatest impact on teacher self-efficiency. In summary, the quality of supervision of teaching and learning should not be neglected, as the findings of the study clearly show that these variables are related to teacher self-efficacy, which cannot be denied as a catalyst for the performance of a school